Building better boyhood programs : evaluation of programs funded by the African American Men and Boys Task Force Initiative - Schultz, Dana (Dana J.); Sontag-Padilla, Lisa (Research report (Rand Corporation), 2015)
African-American youth in Pittsburgh and Allegheny County in Pennsylvania face the same challenges as many of their peers across the country, including poor employment, education, and criminal justice system outcomes. To address these obstacles, human services and community-based programs seek to capitalize on the strengths of youth while recognizing the heterogeneity and interactive nature of both positive and negative individual and environmental influences. While these programs often focus on bolstering youth skills, such as academic motivation, self-esteem, and interpersonal competence, implementing them is challenging, and the degree to which these types of programs are effective is not always clear. This report evaluates the implementation of programs funded by The Heinz Endowment's African American Men and Boys Task Force initiative in Allegheny County and to understand how the programs operated, whether they made progress toward achieving their goals, and what can be learned from their implementation.